Dynamics and Dispersal of Local Human Immunodeficiency Virus Epidemics Within San Diego and Across the San Diego–Tijuana Border. (20th October 2020) - Vrancken, Bram; Mehta, Sanjay R; Ávila-Ríos, Santiago; García-Morales, Claudia; Tapia-Trejo, Daniela; Reyes-Terán, Gustavo; Navarro-Álvarez, Samuel; Little, Susan J; Hoenigl, Martin; Pines, Heather A; Patterson, Thomas; Strathdee, Steffanie A; et al.
Abstract: Background: Evolutionary analyses of well-annotated human immunodeficiency virus (HIV) sequence data can provide insights into viral transmission patterns and associated factors. Here, we explored the transmission dynamics of the HIV-1 subtype B epidemic across the San Diego (US) and Tijuana (Mexico) border region to identify factors that could help guide public health policy. Methods: HIV pol sequences were collected from people with HIV in San Diego County and Tijuana between 1996–2018. A multistep phylogenetic approach was used to characterize the dynamics of spread. The contributions of geospatial factors and HIV risk group to the local dynamics were evaluated. Results: Phylogeographic analyses of the 2034 sequences revealed an important contribution of local transmission in sustaining the epidemic, as well as a complex viral migration network across the region. Geospatial viral dispersal between San Diego communities occurred predominantly among men who have sex with men, with central San Diego being the main source (34.9%) and recipient (39.5%) of migration events. HIV migration was more frequent from San Diego county towards Tijuana than vice versa. Migrations were best explained by the driving time between locations. Conclusions: The US-Mexico border may not be a major barrier to the spread of HIV, which may stimulate coordinated transnational intervention approaches. Whereas a focus on central San Diego has the potential to avert most spread, the substantial viral migration independent of central San Diego shows that county-wide efforts will be more effective. Combined, this work shows that epidemiological information gleaned from pathogen genomes can uncover mechanisms that underlie sustained spread and, in turn, can be a building block of public health decision-making. Abstract : Discrete migration models using human immunodeficiency virus (HIV) sequences show San Diego as a major hub for HIV US-Mexico border region spread, particularly in men who have sex with men. In Mexico, viral migration was more intense towards Tijuana.